The Privatization of Social Security and Women's Welfare: Gender Effects of the Chilean Reform. - de Mesa, Alberto Arenas; Montecinos, Veronica (Latin American Research Review, 1999)
Presents information on a study which showed that the privately managed pension system in Chile has increased gender inequalities. Factors affecting the accumulation of funds in individual retirement accounts; Historical background of the social security system in Chile; Benefits granted to working mothers.